Enhancing father involvement of earthquake-affected fathers: a qualitative analysis - Güloğlu, Mehmet Fatih; Adigüzel, Yusuf (Frontiers in Sociology, 2025)
This study identifies the factors influencing father involvement in container cities following the February 6, 2023 earthquakes in Türkiye and examines the current state of father involvement from a sociological perspective. Father involvement improves children’s cognitive, social and emotional development as well as academic success. However, earthquakes can seriously disturb this. Previous studies have indicated that the father-child relationship transforms after disasters such as earthquakes. This study analyzes, within “father involvement” framework, how father-child relations differs in families forced to set up new life-world in container cities. The analysis was grounded in the phenomenological sociology tradition, which interprets father involvement as a lived sociological phenomenon embedded in everyday experiences. The study utilizes Van Manen’s hermeneutic phenomenological approach. Data collected from 23 earthquake-affected fathers (N = 23), using a semi-structured interview, a purposive sampling technique, and analyzed using MAXQDA. The factors affecting father involvement were thematized as follows: the child’s social and psychological well-being, changes in emotional state, economic deterioration; search for meaning of life, and transformations in relationships with the spouse and the surrounding environment. Father involvement is categorized into three dimensions: responsibility, interaction, and communication. Father involvement is context-dependent, and the factors influencing it differ post-earthquake compared with the existing literature. The earthquake motivated fathers to prioritize their children, highlighting the importance of father involvement.